Studying Townsend and glow modes in an atmospheric-pressure DBD using mass spectrometry. (11th December 2017) - McKay, Kirsty; Donaghy, David; He, Feng; Bradley, James W
Abstract: Ambient molecular beam mass spectrometry has been employed to examine the effects of the mode of operation and the excitation waveform on the ionic content of a helium-based atmospheric-pressure parallel plate dielectric barrier discharge. By applying 10 kHz microsecond voltage pulses with a nanosecond rise times and 10 kHz sinusoidal voltage waveforms, distinctly different glow and Townsend modes were produced, respectively. Results showed a significant difference in the dominant ion species between the two modes. In the Townsend mode, molecular oxygen ions, atomic oxygen anions and nitric oxide anions are the most abundant species, however, in the glow mode water clusters ions and hydrated nitric oxygen anions dominate. Several hypotheses are put forward to explain these differences, including low electron densities and energies in the Townsend mode, more efficient ionization of water molecules through penning ionization and charge exchange with other species in glow mode, and large temperature gradients due to the pulsed nature of the glow mode, leading to more favorable conditions for cluster formation.